Práticas de viés comunicativo em uma sala de aula: reflexões sobre o ensino e aprendizagem de língua inglesa no Ensino fundamental público - Costa, Juliana Patrícia Nunes (2016)
The Foreign Languages teaching presents many difficulties in the scenario of Brazilian public schools, and certain alternatives should be taken to enable the students a learning that may be accessible in their schooling context. The rates in the state of Alagoas lack attention, because they demonstrate the needing of improve learning strategies so that we can achieve better rates. The aim of this study is to establish a proposal of practices focusing on communication classes for teaching and learning English at regular basic public schools as a proposal for changing and intervening in the English classes. The text is divided into four sections. In the first one, we can see all the methodological approach guiding the research, it is the methodology applied to the research itself, starting from the role of Applied Linguistics in the XXI century, entering research in the field of qualitative research methods and going to, the methodological guidelines of data collection. In the second section, I discuss the theoretical process that guides the research, the presentation of topics such as the concept of language as verbal interaction, the English teaching in the public school setting and the concepts relating to methods and approaches for the English language teaching. In the third section, I discuss about the context of the textbook of a foreign language, the approval process and how the teachers choose it in the public school and the problems presented, especially as regards the use of communicative activities. And in the fourth section, I present the discussions on the analysis of data collected, discussing on the reception and development of students to the proposal presented. The results obtained so far show a possible change in students’ learning perspective, through the reflections about English Language teaching and learning in a public school achieved in this research. This way, students realized that orality during English Language classes is possible, and that the development of each activity given can have a favorable outcome, in such a way they can produce spoken language. These factors may already favor the motivation of students in relation to language learning, and social interaction and not just as the assimilation of vocabulary and grammar.